PEMBENTUKAN CITRA POSITIF H. SAHBIRIN NOOR MELALUI GELAR PAMAN BIRIN - Muhammad Ilham Kurniawan (An-Nida : Jurnal Komunikasi Islam, 2021)
Democracy is a system that makes the people as holders of power, Indonesia is a democratic country that determines leaders through general elections for both president and regional head. In the 2015 election, a candidate for governor of South Kalimantan Province H. Sahbirin Noor used the title Paman Birin as an Empathy and Homophily approach to build a positive image of himself, it is interesting to research with the title "The Formation of H. Sahbirin Noor's Positive Image through the Title of Paman Birin", with the formula problem: How is H. Sahbirin Noor's Positive Image Formed through Paman Birin's title. The research objective: To see how the formation of H. Sahbirin Noor's positive image through the title of Paman Birin. With a qualitative approach and descriptive analysis, this study is aimed at analyzing or interpreting written material based on its context. Data is taken from observations, namely making direct observations from studies from books, journals, related news that are published through electronic mass media, or other sources that support this research. Based on the results of the analysis, it was found that, said Paman, it is commonplace in the ears of the public, the embedding of the title of Paman Birin succeeded in building a positive image, reducing distance and causing communication intimacy towards the person of H. Sahbirin Noor for the community, making the majority ethnic group and the wider community accept and making him the winner in the 2015 South Kalimantan Provincial elections.